The Future of Fishermen's Lives: Does it Rely on Inclusive Social Policies to Support Sustainable Societies? - Paramitha, Nurina Adi; Ganefo, Akhmad; Hidayat, Nurul; Mufira, Mila (LPPM Universitas Terbuka, 2024)
Fishermen are often described as people whose lives depend on nature. Since the emergence of gold mines in Pancer, fishermen have had difficulty finding fish. In many cases, the presence of mines in other regions has caused environmental damage. However, there have been no scientific studies that show significant environmental damage due to gold mines in Pancer. This study aims to analyze the lives of fishermen in Pancer after the emergence of gold mines and analyze whether a sustainable society has been realized. The concept of deep ecology is used by researchers to analyze the case. The study uses a qualitative method with a case study approach. Data were obtained from the field using observation and interviews, as well as field documentation including literature studies to support research data. The research was conducted in Pancer Hamlet, especially at Pancer Beach and Pulau Merah Beach. At Pancer Beach, fishermen began to have difficulty finding fish in coastal areas, so they had to sail far to get fish. This caused a decrease in the income of fishermen at Pancer Beach. Meanwhile, at Pulau Merah Beach, the community developed the beach as a tourist destination. Some fishermen switched professions to become traders around the beach or rent boats to tourists. The Pancer community as a sustainable society can be seen from waste management to protect the coastal environment. Support for inclusive social policies from the government is by making various regulations and waste management activities that involve the local society, community groups, stakeholders, including the younger generation. Sustainable society is in line with the concept of deep ecology because it prioritizes the nature sustainability for the sustainability of human's life.